By his words alone the economic consequences of Rodrigo Duterte - Balderas, Elain Brianne O.; Bernardo, Alyanna Maria Belen S.D
Philippine president Rodrigo Duterte has gained worldwide notoriety for his foul-mouthed demeanor, particularly for his threats directed towards the nation’s largest businesses and their powerful owners. Such pronouncements, which may be mistaken for shifts in government policy, may also inadvertently provoke the business sector to react negatively. Whether in fact President Duterte’s business-related pronouncements have had an appreciable effect on the Philippine Stock Exchange Index (PSEi) is the research question pursued in this study. To answer it, we apply an interrupted time series model on PSEi data for the period 30 June 2016 until 31 December 2019 to determine Duterte’s impact on stock prices under six different intervention scenarios. Specifically, we test different classifications of business pronouncements — initial business pronouncements, anti-oligarch statements, personal attacks, and combinations of the three. The results show that there exists a significant relationship between Duterte’s negative business-related pronouncements on the PSEi closing price, with the biggest changes reflected the first times he brought up a particular issue or addressed a certain personality. To supplement our findings, we also calculate the aggregate wealth losses for the period of 2018-2019, and estimate a total cost of Php 1M instantaneously for the five pronouncements we observed. After five days, these losses increased by 69.72% to Php 47M, then by 364.51% to Php 441M after ten days. We also find that, after a ten-day adjustment period, the losses accumulated in the Philippine stock market after Duterte’s pronouncements accumulate to 0.0027% of Gross Domestic Product (GDP).